Effects of foundation settlement on comfort of riding on high-speed train-track-bridge coupled systems. Issue 8 (3rd August 2022) - Zheng, Lan; Jiang, Lizhong; Feng, Yulin; Liu, Xiang; Lai, Zhipeng; Zhou, Wangbao
Abstract: In this study, the principle of minimum potential energy has been used to deduce the mapping relationship between beam deformation and rail deformation with consideration of the constraint effects of a subgrade system. Based on the above mapping relationship, a dynamic simulation analysis on the train-track-bridge coupled system has been carried out. Taking the index of riding comfort as the investigation object, in combination with the specified limits in the relevant specification, an analysis has been carried out to determine the control threshold of beam deformation of high-speed railways. According to the simulation results, the dynamic response of different types of high-speed trains shows significantly different sensitivities to the pier settlement and the beam faulting. The threshold value in settlement control in the case of simultaneous settlement of two adjacent piers is smaller than that in the case of the single-pier settlement. Under the operating condition of beam faulting, the wheel unloading rate is more sensitive to the faulting of the beams than the vertical acceleration and Sperling's ride index. To avoid the vertical acceleration specified limit of car body, it is recommended to maintain the pier settlement to less than 9.7 mm, and the beam faulting to less than 5.3 mm.